Iterated Greedy for The Two-Echelon Electric Vehicle Routing Problem with Time Windows - Junqueira, Igor de Andrade; Bernardino, Heder Soares; Moreno, Lorenza Leão Oliveira; Gonçalves, Luciana Brugiolo; Soares, Stênio Sã Rosário F. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2023: Anais do XX Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2023.234252, 2023)
Cargo transportation can be very challenging in big cities due to congestion, pollution, and the prohibition of circulation at certain times of the day. Many transportation models can help to improve these issues. An example is the Two-Echelon Electric Vehicle Routing Problem with Time Windows (2E-EVRPTW), which combines Electric Vehicles (EVs) with small capacity and Combustion Vehicles (CVs) with large capacity and range. These types of vehicles are combined in the solution using satellites, which are intermediary depots. The satellites attend to customers using EVs, and the satellites are attended by CVs that leave the central depot. As EVs have a limited range due to their batteries, recharging stations can be used. We propose here an Iterated Greedy (IG) with destroy and repair operators only. We compare the proposed IG with two Variable Neighborhood Search approaches from the literature, and the proposal obtained better results, both concerning distance (objective function) and CPU time.